The Effect of E-Learning on Students’ Immediate and Postponed Achievement in Physics in Jordanian Secondary Schools - AlShannag, Qasim; Bani Domi, Hassa (Jordan Journal of Educational Sciences, 2006)
This study aimed at investigating the effect of e-learning on scientific track secondary school students’ immediate and postponed achievement in physics. The study sample consisted of (118) male students distributed into five groups at three secondary schools for boys in Al-Karak governorate. Four of these groups are experimental (internet, CD, internet + CD, the teacher + Data Show) and one control group (traditional method). In order to achieve the objectives of the study, a physics concept achievement test was used after confirming its validity and reliability. The mean scores, standard deviations, t-test, ANCOVA were used in the statistical analysis. Results showed that there is a significant statistical difference (α = 0.05) between the mean scores of the performance of first secondary scientific track students on the post physics concepts achievement test due to method of learning. The difference was in favor of learning by using CD compared to using the traditional method. Yet there is non statistically significant difference due to method of learning using internet, teacher + Data Show, and internet + CD compared to the traditional method. And showed that there isn’t any statistical significance at (α =0.05) among the experimental groups on the achievement delayed test on physics concepts compared with the traditional method. However, there is statistically significant analysis difference between the mean scores of students on the physics concepts achievement postponed post test in favor of the post test. This indicates that the methods of e-learning are not effective in helping students in retaining information.